Propylene-based copolymer compositions
By fine-tuning the composition of propylene, ethylene copolymer and talc, the problems of uneven optical characteristics and sterilization in the extrusion blow molding process are solved, and the balance between softness and optical properties is achieved, which is suitable for the production of high-quality Blow-molded items and medical products.
Patent Information
- Application Number
- CN202380038203.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-06
- Filing Date
- 2023-05-29
- Publication Date
- 2024-12-13
AI Technical Summary
The optical properties of the extruded blow molding process products are uneven, resulting in a decrease in gloss and transparency, and the sterilization process has an impact on optical properties, making it difficult to balance between maintaining softness and improving optical properties.
Using 74-89% propylene and ethylene copolymer composition, by fine-tuning the ethylene-derived unit content, melting temperature, melt flow rate and xylene soluble content, combined with 0.1-10,000 ppm talc to form a specific particle size distribution and Compositions with specific surface area are suitable for the production of blow molded articles and post-sterilization medical products.
While maintaining the balance of flexural modulus and haze, the optical properties of the composition are significantly improved, the gloss and transparency of blow-molded products are improved, suitable for the production of soft blow-molded items such as bottles, and maintained well after sterilization. optical properties.
Smart Images

Figure BDA0005116518070000061 
Figure BDA0005116518070000101 
Figure BDA0005116518070000121
Abstract
Description
Technical Field
[0001] The present disclosure relates to a composition comprising a propylene ethylene copolymer and talc. The composition has particularly good optical properties in addition to mechanical properties, and in particular the composition can be sterilized to maintain good optical and mechanical properties. The composition is particularly suitable for producing blow molded articles, in particular bottles. Background Art
[0002] It is well known in the polymer field that different applications require specially tailored polymers to achieve the individual, more demanding properties. For example, a polymer used for injection molding must have other properties that are different from a polymer used for blow molding.
[0003] For example, the extrusion blow molding process is a very specific process that allows bottles of different sizes and shapes to be produced in a flexible and inexpensive manner. A major disadvantage of this process is the complex curing step compared to conventional injection molding.
[0004] Therefore, extrusion blow molded articles (such as bottles) generally exhibit inferior optical properties compared to any injection molded articles. For example, the surface properties of the interior and / or exterior of an extrusion blow molded bottle are generally non-uniform (flow lines, melt fracture), resulting in reduced overall gloss and clarity compared to an injection molded bottle or an injection stretch blow molded bottle. When it is desired to produce a soft article, the article must have low haze and low flexural modulus. High flexural modulus products are generally associated with low haze, so when it is desired to reduce the flexural modulus in order to obtain a soft product, the haze becomes worse.
[0005] Then, the medical article needs to be sterilized, and it is well known in the art that sterilization will have some deteriorating effects on the optical properties.
[0006] Therefore, it is desirable to have a polymer that exhibits a specific balance of flexural modulus and haze, such that optical properties can be improved even at lower modulus. Additionally, there is a need to improve optical properties after sterilization.
[0007] US2005 / 0113517 relates to a polyolefin-based biaxially oriented multilayer film having at least one surface layer comprising a propylene-ethylene copolymer comprising:
[0008] 30 to 70 wt% of a propylene-ethylene random copolymer component having an ethylene content of 1 to 7 wt% and
[0009] 70 to 30% by weight of a low crystalline or amorphous propylene-ethylene random copolymer component.
[0010] The composition may contain additives such as talc in an amount of 0.0001% to 3% by weight.
[0011] Applicants have discovered that by fine-tuning various parameters, a balance can be achieved between the optical properties and the softness of the composition. Summary of the invention
[0012] Therefore, the object of the present disclosure is a polyolefin composition comprising:
[0013] A) 74 to 89 wt. % of a copolymer of propylene and ethylene, wherein:
[0014] i) a content of ethylene-derived units of from 3.3 wt% to 6.0 wt% as measured by NMR;
[0015] (ii) a melting temperature ranging from 132° C. to 143° C. as measured by DSC;
[0016] (iii) melt flow rate (230°C / 2.16 kg. ISO 1133) ranging from 1.1 g / 10 min to 3.5 g / 10 min;
[0017] (iv) a xylene soluble content at 25° C. ranging from 4.0 wt % to 10.0 wt %;
[0018] B) 11 to 26 wt% of a propylene ethylene copolymer containing 18.0 to 28.0 wt% of ethylene-derived units as measured by NMR;
[0019] The obtained polyolefin composition has:
[0020] i) a content of ethylene-derived units of 5.0 wt% to 7.3 wt% as measured by NMR;
[0021] ii) a content of ethylene-derived units in the fraction soluble in xylene at 25°, measured by NMR, of from 20.3% to 28.0% by weight;
[0022] iii) melt flow rate (ISO 1133 (230°C, 2.16 kg) in the range of 1.0 g / 10 min to 4.0 g / 10 min;
[0023] iv) a xylene soluble matter at 25°C ranging from 13 wt% to 25.0 wt%;
[0024] v) the intrinsic viscosity of said fraction soluble in xylene at 25°C, measured in tetralin at 135°C, ranges from 0.6 dl / g to 2.5 dl / g;
[0025] The sum of A+B is 100;
[0026] C) from 10000 ppm to 100 ppm of talc having a particle size distribution comprised between 0.5 μm and 5 μm and a particle size distribution greater than 15 μm measured with a SediGraph 5100 particle size analysis system. 2 / g specific surface area BET (ISO 9277:2010);
[0027] ppm is calculated as the sum of the amounts of A+B. DETAILED DESCRIPTION
[0028] Therefore, the object of the present disclosure is a polyolefin composition comprising:
[0029] A) 74 to 89 wt.-%, preferably 75 to 87 wt.-%, more preferably 76 to 85 wt.-% of a copolymer of propylene and ethylene, wherein:
[0030] i) a content of ethylene-derived units measured by NMR of 3.3 to 6.0 wt%; preferably 3.5 to 5.5 wt%; more preferably 3.7 to 4.8 wt%;
[0031] (ii) a melting temperature as measured by DSC ranging from 132°C to 143°C; preferably ranging from 134°C to 142°C; more preferably ranging from 136°C to 141°C;
[0032] (iii) melt flow rate (230°C / 2.16kg.ISO 1133) ranging from 1.1 g / 10 min to 3.5 g / 10 min; preferably ranging from 1.2 g / 10 min to 2.5 g / 10 min; more preferably ranging from 1.3 g / 10 min to 2.0 g / 10 min;
[0033] (iv) xylene solubles at 25°C range from 4.0 wt% to 10.0 wt%; preferably range from 4.5 wt% to 9.0 wt%; more preferably range from 5.2 wt% to 8.0 wt%;
[0034] B) 11 to 26 wt%, preferably 13 to 25 wt%, more preferably 15 to 24 wt% of a propylene ethylene copolymer containing 18.0 to 28.0 wt%, preferably 20.2 to 26.3 wt%, more preferably 20.8 to 25.8 wt% of ethylene derived units as measured by NMR;
[0035] The obtained polyolefin composition has:
[0036] i) a content of ethylene-derived units measured by NMR of 5.0 to 7.3 wt%; preferably 5.3 to 7.2 wt%; more preferably 5.5 to 7.2 wt%;
[0037] ii) the content of ethylene-derived units in the fraction soluble in xylene at 25°, measured by NMR, is from 20.3% to 28.0% by weight; preferably from 21.4% to 27.7% by weight,
[0038] More preferably, 22.3 wt% to 26.3 wt%;
[0039] iii) melt flow rate (ISO 1133 (230°C, 2.16 kg) ranges from 1.0 g / 10 min to 4.0 g / 10 min; preferably ranges from 1.1 g / 10 min to 2.9 g / 10 min; more preferably ranges from 1.2 g / 10 min to 2.5 g / 10 min;
[0040] iv) xylene solubles at 25°C ranging from 13 wt% to 25.0 wt%; preferably ranging from 15 wt% to 22.0 wt%; more preferably ranging from 16 wt% to 20.0 wt%;
[0041] v) the intrinsic viscosity of the fraction soluble in xylene at 25°C, measured in tetralin at 135°C, ranges from 1.6 dl / g to 3.2 dl / g; preferably ranges from 1.8 dl / g to 3.1 dl / g; more preferably ranges from 2.0 dl / g to 2.8 dl / g;
[0042] The sum of A+B is 100;
[0043] C) talc from 10000 ppm to 100 ppm; preferably from 8000 ppm to 300 ppm; more preferably from 4000 PPM to 500 ppm; having a particle size distribution of 0.5 to 5 μm measured with a SediGraph 5100 particle size analysis system and a specific surface area BET (ISO 9277:2010) higher than 15 m 2 / g; preferably at 15m 2 / g to 25m 2 / g range; preferably 16m 2 / g to 23m 2 / g; more preferably 17m 2 / g to 21m 2 / g;
[0044] The term copolymer necessarily refers to binary copolymers containing two monomers (propylene and ethylene).
[0045] The polyolefin composition of the invention is particularly suitable for producing blow-molded articles, in particular bottles. Furthermore, the composition is particularly suitable for sterilization to obtain medical articles. The sterilization process comprises a step of heating the polymer at 121°C for 30 minutes.
[0046] The polyolefin composition preferably has one or more of the following characteristics:
[0047] The haze before sterilization measured on a 1 mm plate according to the method disclosed in the examples ranges from 30.0% to 65.0%, preferably ranges from 35.0% to 59.0%, and more preferably ranges from 40.0% to 52.0%;
[0048] ii) a flexural modulus (ASTM D 790) ranging from 450 MPa to 770 MPa; preferably from 500 MPa to 740 MPa; even more preferably from 520 MPa to 720 MPa;
[0049] iii) The Charpy impact strength at 23°C ranges from 65 kj / m 2 Up to 100.0 kj / m 2 ; preferably in the range of 70.0 kj / m 2 Up to 95.0 kj / m 2 ; More preferably, the range is from 75.0 kj / m 2 Up to 93.0 kj / m 2 ;
[0050] iv) There is only one melting point in the DSC thermogram measured according to the method described in the examples.
[0051] v) The difference between the haze measured before sterilization and the haze measured after sterilization is in the range of 8.0% to 20.0%, preferably 9.0% to 17.0%; more preferably 10.0% to 14.5%.
[0052] The polyolefin composition of the present invention is particularly suitable for obtaining small blow-molded articles, such as bottles.
[0053] Another object of the present invention is therefore a bottle comprising the composition according to the invention.
[0054] Small blow molded articles can be manufactured by various industrial processes known in the art.
[0055] The composition of the present invention can be prepared by blending components A) and B).
[0056] The polymerization of A) and B) can be carried out in the presence of a Ziegler-Natta catalyst. An essential component of the catalyst is a solid catalyst component comprising a titanium compound having at least one titanium-halogen bond and an electron donor compound, both of which are supported in active form on a magnesium halide. Another essential component (cocatalyst) is an organoaluminum compound, such as an alkylaluminum compound.
[0057] An external donor may be added optionally.
[0058] The catalysts typically used in the process of the present invention are capable of producing polypropylene having a xylene insolubility value at ambient temperature greater than 90%, preferably greater than 95%.
[0059] Catalysts having the above characteristics are well known in the patent literature; particularly advantageous are the catalysts described in US Pat. No. 4,399,054 and European Patent No. 45977. Other examples can be found in US Pat. No. 4,472,524.
[0060] The solid catalyst component used in the catalyst comprises as an electron donor (internal donor) a compound selected from the group consisting of ethers, ketones, lactones, compounds containing N, P and / or S atoms, and esters of mono- and dicarboxylic acids.
[0061] Particularly suitable electron donor compounds are esters of phthalic acid and 1,3-diethers of the following formula:
[0062]
[0063] Where R I and R II Same or different and C 1 -C 18 Alkyl, C 3 -C 18 Cycloalkyl or C 7 -C 18 Aryl radical; R III and R IV Same or different and C 1 -C 4an alkyl radical; or a 1,3-diether in which the carbon atom in position 2 belongs to a cyclic or polycyclic structure consisting of 5, 6 or 7 carbon atoms or 5-n or 6-n' carbon atoms and n nitrogen atoms and n' heteroatoms selected from the group consisting of N, O, S and Si, respectively, wherein n is 1 or 2 and n' is 1, 2 or 3, said structure containing two or three degrees of unsaturation (cyclopolyene structure) and optionally condensed with other cyclic structures or substituted with one or more substituents selected from the group consisting of linear or branched alkyl radicals, cycloalkyl, aryl, aralkyl, alkaryl radicals and halogen, or condensed with other cyclic structures and substituted with one or more of the above substituents, one or more of which may also be bonded to the condensed cyclic structure; one or more of the above alkyl, cycloalkyl, aryl, aralkyl or alkaryl radicals and a condensed cyclic structure optionally containing one or more heteroatoms as substituents for carbon atoms or hydrogen atoms or both.
[0064] Ethers of this type are described in published European Patent Applications 361,493 and 728,769.
[0065] Representative examples of the diethers are 2-methyl-2-isopropyl-1,3-dimethoxypropane, 2,2-diisobutyl-1,3-dimethoxypropane, 2-isopropyl-2-cyclopentyl-1,3-dimethoxypropane, 2-isopropyl-2-isopentyl-1,3-dimethoxypropane, 9,9-bis(methoxymethyl)fluorene.
[0066] Other suitable electron donor compounds are phthalic acid esters, such as diisobutyl phthalate, dioctyl phthalate, diphenyl phthalate and benzyl butyl phthalate.
[0067] The preparation of the above-mentioned catalyst components is performed according to various methods.
[0068] For example, MgCl2.nROH adduct (especially in the form of spherical particles) (where n is generally from 1 to 3 and ROH is ethanol, butanol or isobutanol) is reacted with an excess of TiCl4 containing an electron donor compound. The reaction temperature is generally 80° C. to 120° C. The solid is then separated and reacted once more with TiCl4 in the presence or absence of an electron donor compound, after which it is separated and washed with an aliquot of a hydrocarbon until all chloride ions are gone.
[0069] In the solid catalyst component, the titanium compound, denoted Ti, is generally present in an amount of 0.5 to 10% by weight. The amount of electron donor compound remaining fixed on the solid catalyst component is generally 5 to 20 mol% relative to the magnesium dihalide.
[0070] Titanium compounds which can be used for the preparation of the solid catalyst component are titanium halides and halogen alcoholates. Titanium tetrachloride is the preferred compound.
[0071] The above reactions form magnesium halides in active form. Other reactions are known in the literature which, starting from magnesium compounds other than halides, such as magnesium carboxylates, form magnesium halides in active form.
[0072] Al-alkyl compounds used as co-catalysts include Al-trialkyls such as Al-triethyl, Al-triisobutyl, Al-tri-n-butyl and linear or cyclic Al-alkyl compounds containing two or more Al atoms bonded to each other via O or N atoms or SO4 or SO3 groups.
[0073] The Al-alkyl compound is generally used in such an amount that the Al / Ti ratio is 1 to 1000.
[0074] Electron donor compounds that can be used as external donors include aromatic acid esters, such as alkyl benzoates, and in particular silicon compounds containing at least one Si-OR bond, wherein R is a hydrocarbon radical.
[0075] Examples of silicon compounds are (tert-butyl)2Si(OCH3)2, (cyclohexyl)(methyl)Si(OCH3)2, (cyclopentyl)2Si(OCH3)2 and (phenyl)2Si(OCH3)2 and (1,1,2-trimethylpropyl)Si(OCH3)3.
[0076] 1,3-Diethers of the abovementioned formula can also be used advantageously. If the internal donor is one of these diethers, the external donor can be omitted.
[0077] In particular, component A) is preferably prepared by using a catalyst containing a phthalate as internal donor and (cyclopentyl)2Si(OCH3)2 as external donor, or the 1,3-diether as internal donor, even though many other combinations of the aforementioned catalyst components may allow obtaining the composition according to the invention.
[0078] The Ziegler-Natta catalyst that can be used to prepare the propylene polymer of the present invention is a solid catalyst component comprising a magnesium halide, a titanium compound having at least one titanium-halogen bond as described above and at least two electron donor compounds, one of which is selected from succinates and the other is selected from 1,3-diethers.
[0079] It is also possible to prepare components (A) and (B) in a continuous sequential polymerization process, wherein component A) is prepared in a first reactor and component (B) is prepared in a second reactor in the presence of component A) according to known techniques and operating in the gas phase or in the liquid phase with or without an inert diluent, or by a mixed liquid-gas technique.
[0080] Component C) may be a commercial product.
[0081] The following examples are given for illustration of the present invention and not for limiting purposes.
[0082] Examples
[0083] Characterization methods
[0084] Melting temperature and crystallization temperature: determined by differential scanning calorimetry (DSC)
[0085] Weigh 6±1 mg of sample, heat to 220±1°C at a rate of 20°C / min in a nitrogen stream and keep at 220±1°C for 2 minutes, then cool to 40±2°C at a rate of 20°C / min, and keep at this temperature for 2 minutes to crystallize the sample. Then, heat to 220°C±1 at a rate of 20°C / min to melt the sample again. Record the melting scan, obtain the thermogram, and read the melting temperature and crystallization temperature from it.
[0086] Melt flow rate: measured according to method ISO 1133 (230°C, 5 kg).
[0087] Xylene soluble fraction at 25°C (XS)
[0088] The xylene solubles at 25°C have been determined according to ISO 16152:2005; the solution volume is 250 ml, precipitation is carried out at 25°C for 20 minutes, with 10 minutes of stirring (magnetic stirrer) of the solution, and drying at 70°C.
[0089] Intrinsic viscosity (IV)
[0090] The sample was dissolved in tetralin at 135°C and then poured into a capillary viscometer.
[0091] The viscometer tube (Ubbelohde type) is surrounded by a cylindrical glass jacket; this setup allows temperature control with a circulating thermostatic liquid.
[0092] The downward passage of the meniscus is timed by a photoelectric device. The meniscus' passage in front of the upper lamp starts a counter with a quartz crystal oscillator. When it passes the lower lamp, the meniscus stops the counter and the outflow time is recorded: This is converted to an intrinsic viscosity value by the following method
[0093] Haze (on 1mm plate)
[0094] According to the method used, 5×5 cm specimens are cut into 1 mm thick molded plaques and the haze value is measured using a Gardner photometric device connected to a UX-10 Hazemeter or an equivalent instrument with a GE1209 light source and filter "C". Reference samples of known haze are used to calibrate the instrument. The plaques to be tested are produced according to the following method.
[0095] Plaques of 75 x 75 x 1 mm were molded using a 90 ton GBF Plastiniector G235190 injection molding machine under the following processing conditions:
[0096] Screw speed: 120rpm
[0097] Back pressure: 10 bar
[0098] Melting temperature: 260℃
[0099] Injection time: 5 seconds
[0100] Switch to holding pressure: 50 bar
[0101] First stage holding pressure: 30 bar
[0102] Second stage pressure: 20 bar
[0103] Maintain pressure curve: 5 seconds in the first stage
[0104] Second stage 10 seconds
[0105] Cooldown: 20 seconds
[0106] Mold water temperature: 40℃
[0107] Ethylene content in copolymer
[0108] The data were collected on a Bruker AV-600 spectrometer equipped with a cryoprobe. 13 C NMR spectroscopy, operated at 160.91 MHz at 120 °C in Fourier transform mode.
[0109] Sββ carbon (according to "through 13C NMR measures monomer sequence distribution in ethylene-propylene rubber. 3. Use of Reaction Probability Mode" CJ Carman, RA Harrington and CE Wilkes, Macromolecules, 1977, vol. 10, p. 536) peak was used as an internal reference with a value of 29.9 ppm. The sample was dissolved in 1,1,2,2-tetrachloroethane-d2 at 120°C at a concentration of 8% wt / v. Each spectrum was acquired with a 90° pulse with a 15 s delay between the pulse and the CPD to eliminate 1 H- 13 C coupling. 512 transient data were stored in 32K data points using a spectral window of 9000 Hz.
[0110] According to Kakugo ("Carbon-13 NMR determination of monomer sequence distribution in ethylene-propylene copolymers prepared with δ-titaniumtrichloride-diethyl-aluminum chloride", M. Kakugo, Y. Naito, K. Mizunuma and T. Miyatake, Macromolecules, 1982, No. 15, p. 1150), the spectra were assigned using the following equations, and the triad distribution and composition were evaluated:
[0111] PPP=100Tββ / S PPE=100Tβδ / S EPE=100Tδδ / S
[0112] PEP=100Sββ / S PEE=100Sβδ / S EEE=100(0.25Sγδ+0.5Sδδ) / S
[0113] S=Tββ+Tβδ+Tδδ+Sββ+Sβδ+0.25Sγδ+0.5Sδδ
[0114] The mole percentage of ethylene content was estimated using the following equation:
[0115] E%mol=100*[PEP+PEE+EEE]. The weight percent of ethylene content was estimated using the following equation:
[0116] 100*E%mol*MWE
[0117] E%wt.=E%mol*MWE+P%mol*MWP
[0118] Where P%mol is the molar percentage of propylene content, and MWE and MWP are the molecular weights of ethylene and propylene, respectively.
[0119] The product of the reactivity ratios r1r2 is calculated according to Carman (CJ Carman, RA Harrington and CE Wilkes, Macromolecules, 1977; No. 10, p. 536) as follows:
[0120]
[0121] According to PPP mmT ββ (28.90 to 29.65ppm) and total T ββ The stereoregularity of the propylene sequence was calculated as the mm content by the ratio of (29.80 to 28.37 ppm).
[0122] Impact test: ISO 180
[0123] Preparation of injection molded specimens: Specimens of 80×10×4 mm were obtained according to method ISO 1873-2:2007.
[0124] Charpy impact test at 23°C: measured on injection molded specimens according to ISO 179-1:2010.
[0125] Flexural modulus
[0126] Flexural modulus is measured according to ISO 178 with additional conditions according to ISO 1873-2 on injection molded specimens.
[0127] Specific surface area BET
[0128] Measured according to ISO 9277:2010.
[0129] Particle size distribution
[0130] The measurements were performed using a SediGraph 5100 particle size analysis system.
[0131] Example 1 according to the present invention
[0132] Catalyst system
[0133] The Ziegler-Natta catalyst was prepared according to Example 5, lines 48 to 55 of European Patent EP728769. Triethylaluminum (TEAL) was used as a cocatalyst and dicyclopentyldimethoxysilane (DCPMS) as an external donor in the weight ratios shown in Table 1.
[0134] Prepolymerization
[0135] Before the solid catalyst component is introduced into the polymerization reactor, it is suspended in liquid propylene at 20°C for about 5 minutes and then introduced into the first polymerization reactor for prepolymerization.
[0136] polymerization
[0137] The polymerization experiments were carried out in a series of three reactors in a continuous mode, equipped with means to transfer the product from one reactor to another reactor next to it. The first two reactors were liquid phase reactors, and the third was a fluidized bed gas phase reactor. Component (A) was prepared in the first and second reactors, which had the same polymerization parameters, while component (B) was prepared in the third reactor.
[0138] Hydrogen was used as a molecular weight regulator.
[0139] The gas phase (propylene, ethylene and hydrogen) was analyzed continuously by gas chromatography.
[0140] At the end of the experiment, the powder was discharged and dried under a stream of nitrogen.
[0141] The main polymerization conditions are reported in Table 1.
[0142] Table 1
[0143]
[0144] C2 = ethylene; C3 = propylene; H2 = hydrogen
[0145] Table 2 reports the characteristics of the composition of Example A
[0146] Examples Example A Component A) Splinter Ethylene content weight% 4.0 MFR g / 10' 1.4 Xylene soluble matter at 25℃ weight% 6.0 Melting temperature ℃ 139.1 Component B) Splinter weight% 14.5 Ethylene content in component b)* weight% 21.8 Characteristics of the composition Xylene soluble matter at 25℃ weight% 16.8 MFR g / 10' 1.26 XSIV (XS intrinsic viscosity) dl / g 2.18 Ethylene content in the xylene soluble fraction weight% 25.2 Ethylene content weight% 6.4
[0147] **Calculated
[0148] The composition of Example A has been blended with talc (component C) having a particle size distribution of 0.5 to 5 μm and 18 μm 2 As a comparative example, a particle size distribution of 0.5 to 5 μm and 13 m 2 / g surface area (BETT) of commercial talc HM05.
[0149] The analysis results of the composition characteristics are shown in Table 3
[0150] Table 3
[0151]
[0152] Comparative Example 1 Composition without talc By comparing the examples according to the present invention and the comparative examples, the haze after sterilization in the examples according to the present invention is lower.
Claims
1. A polyolefin composition comprising: A) 74 to 89 wt. % of a copolymer of propylene and ethylene, wherein: i) a content of ethylene-derived units of from 3.3 wt% to 6.0 wt% as measured by NMR; (ii) a melting temperature ranging from 132° C. to 143° C. as measured by DSC; (iii) melt flow rate (230°C / 2.16 kg. ISO 1133) ranging from 1.1 g / 10 min to 3.5 g / 10 min; (iv) a xylene soluble content at 25° C. ranging from 4.0 wt % to 10.0 wt %; B) 11 to 26 wt% of a propylene ethylene copolymer containing 18.0 to 28.0 wt% of ethylene-derived units as measured by NMR; The obtained polyolefin composition has: i) a content of ethylene-derived units of 5.0 wt% to 7.3 wt% as measured by NMR; ii) a content of ethylene-derived units in the fraction soluble in xylene at 25°, measured by NMR, of from 20.3% to 28.0% by weight; iii) melt flow rate (ISO 1133 (230°C, 2.16 kg) in the range of 1.0 g / 10 min to 4.0 g / 10 min; iv) a xylene soluble matter at 25°C ranging from 13 wt% to 25.0 wt%; v) the intrinsic viscosity of said fraction soluble in xylene at 25°C, measured in tetralin at 135°C, ranges from 0.6 dl / g to 2.5 dl / g; The sum of A+B is 100; C) from 10000 ppm to 100 ppm of talc having a particle size distribution comprised between 0.5 μm and 5 μm and a specific surface area BET (ISO 9277:2010) higher than 15 m2 / g, measured with a SediGraph 5100 particle size analysis system; ppm is calculated as the sum of the amounts of A+B.
2. The polyolefin composition according to claim 1, wherein the content of ethylene-derived units in component A) ranges from 3.5 wt.-% to 5.5 wt.-%.
3. The polyolefin composition according to any one of claims 1 to 2, wherein in component A), the melt flow rate (230°C / 2.16 kg. ISO 1133) ranges from 1.2 g / 10 min to 2.5 g / 10 min.
4. The polyolefin composition according to any one of claims 1 to 4, wherein in component A), the xylene solubles at 25°C range from 4.5 wt% to 9.0 wt%.
5. The polyolefin composition according to any one of claims 1 to 5, wherein in component B), the ethylene-derived units content ranges from 20.2 wt% to 26.3 wt%.
6. The polyolefin composition according to any one of claims 1 to 5, wherein the content of ethylene derived units measured by NMR is from 5.3 to 7.2 wt%.
7. The polyolefin composition according to any one of claims 1 to 6, wherein the content of ethylene-derived units in the fraction soluble in xylene at 25° measured by NMR is between 21.4% and 27.7% by weight.
8. The polyolefin composition according to any one of claims 1 to 7, wherein the melt flow rate (ISO 1133 (230°C, 2.16 kg)) ranges from 1.1 g / 10 min to 2.9 g / 10 min.
9. The polyolefin composition according to any one of claims 1 to 8, wherein the xylene solubles at 25°C range from 15 wt% to 22.0 wt%.
10. The polyolefin composition according to any one of claims 1 to 9, wherein the intrinsic viscosity of the fraction soluble in xylene at 25°C measured in tetralin at 135°C ranges from 1.8 dl / g to 3.1 dl / g.
11. The polyolefin composition according to any one of claims 1 to 10, wherein in component A), the melting temperature measured by DSC ranges from 134°C to 142°C.
12. The polyolefin composition according to any one of claims 1 to 11, wherein the content of ethylene derived units measured by NMR is from 5.5 to 7.2 wt%.
13. The polyolefin composition according to any one of claims 1 to 12, wherein in component C), talc has a specific surface area of BET (ISO 9277:2010) in the range of 15 m 2 / g to 25m 2 / g.
14. A small blow-molded article comprising the polyolefin composition according to any one of claims 1 to 12.
15. A bottle comprising the polyolefin composition according to any one of claims 1 to 12.
